Data-sensitive visual navigation. (October 2017) - Mindek, Peter; Mistelbauer, Gabriel; Gröller, Eduard; Bruckner, Stefan
Highlights: A model for navigation sensitive to the underlying data is proposed. A user-interface element, TreeSlider, for traversing tree structures is proposed. The data-sensitive navigation model is applied to various user-interface elements. Graphical abstract: Abstract: In visualization systems it is often the case that the changes of the input parameters are not proportional to the visual change of the generated output. In this paper, we propose a model for enabling data-sensitive navigation for user-interface elements. This model is applied to normalize the user input according to the visual change, and also to visually communicate this normalization. In this way, the exploration of heterogeneous data using common interaction elements can be performed in an efficient way. We apply our model to the field of medical visualization and present guided navigation tools for traversing vascular structures and for camera rotation around 3D volumes. The presented examples demonstrate that the model scales to user-interface elements where multiple parameters are set simultaneously.